2017
DOI: 10.3892/or.2017.5809
|View full text |Cite
|
Sign up to set email alerts
|

Musashi1, a potential prognostic marker in esophageal squamous cell carcinoma

Abstract: Esophageal cancer ranks as the sixth leading cause of cancer-related deaths worldwide. Cancer stemness is mainly considered to be the key factor for cancer recurrence particularly in esophageal cancer. It is important to identify cancer stem cell markers as targets in future therapies. The present study aimed to investigate the expression of putative cancer stem cell-related marker musashi1 (Msi1) and assess the correlation with clinicopathologcal status of esophageal squamous cell carcinoma (ESCC) cases. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Previous studies have proven that RNA-binding proteins are crucial for cell proliferation and apoptosis during the process of tumorigenesis (23-25). As a member of the MSI family of RNA-binding proteins, MSI1 was found to be overexpressed in several types of cancer, including non-small-cell lung cancer (14), osteosarcoma (21), and esophageal SCC (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have proven that RNA-binding proteins are crucial for cell proliferation and apoptosis during the process of tumorigenesis (23-25). As a member of the MSI family of RNA-binding proteins, MSI1 was found to be overexpressed in several types of cancer, including non-small-cell lung cancer (14), osteosarcoma (21), and esophageal SCC (17).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that tumor stem cells are responsible for tumor metastasis (6,7), and an increasing number of stem cell-related genes have been proven to be involved in tumorigenesis (8,9). MSI1 is a RNA-binding protein of the Musashi family that has been found to be associated with certain cancers, including glioma (10), cervical cancer (11), gastric cancer (12) and lung cancer (13,14). In addition, MSI1 appears to be a prognostic marker for esophageal SCC (15) and glioma (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive research in the past few decades has identified CSCs in multiple solid tumors, including colon [ 30 ], brain [ 31 ], lung [ 32 ], liver [ 33 ], and other cancers [ 34 ]. CSCs are generally defined by their distinct and specific surface antigen expression [ 35 , 36 , 37 ] and by their capacity to generate spherical colonies from single cell in suspension cultures [ 38 ]. Moreover, CSCs exhibit a higher resistance to standard chemotherapy [ 39 ] and radiation therapy [ 40 ] through deregulated apoptosis and survival signaling.…”
Section: Cancer Stem Cells: Implications For Hepatocarcinogenesismentioning
confidence: 99%
“…In contrast, it has been reported that there was increased expression of MSI1 in Chinese ESCC samples compared with normal margins. Moreover, there were significant correlations between stage, lymph node involvement, and the levels of MSI1 expression [39].…”
Section: Main Textmentioning
confidence: 99%